2013
DOI: 10.1177/0271121413477498
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Language and Literacy Skills Among Children With Disabilities in Inclusive Early Reading First Classrooms

Abstract: Quality literacy instruction in preschool can be critical to the future academic success for all children, but may be even more so for children with disabilities. The purpose of this study was to examine progress in emergent literacy skills of young children with disabilities, compared with their typical peers, in an inclusive preschool setting. Participants in this study included 77 prekindergarteners with disabilities and 77 children with no identified disabilities who were matched based on age, teacher, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Theoretically, inclusive ECE settings, particularly federally or locally regulated center-based programs, give doubly vulnerable children ample opportunities to initiate, model, and extend their oral language skills (Bulotsky-Shearer et al, 2012) and build social skills and relationships (Odom, 2000) with typically developing peers. For these children with the most “room to grow,” interactions with more skilled peers and teachers offer the chance to hear and experiment with more complex language and early literacy concepts (Green et al, 2013; Holahan & Costenbader, 2000; Phillips & Meloy, 2012). Inclusive center-based ECE also provides the stage for children’s first encounters with unfamiliar peers and thus serves as a proving ground for the development of empathy, acceptance, tolerance, and social skills (Hauser-Cram et al, 1993; Killen et al, 2011; Odom et al, 2004; Stoneham, 2001).…”
Section: Double Vulnerability In Early Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, inclusive ECE settings, particularly federally or locally regulated center-based programs, give doubly vulnerable children ample opportunities to initiate, model, and extend their oral language skills (Bulotsky-Shearer et al, 2012) and build social skills and relationships (Odom, 2000) with typically developing peers. For these children with the most “room to grow,” interactions with more skilled peers and teachers offer the chance to hear and experiment with more complex language and early literacy concepts (Green et al, 2013; Holahan & Costenbader, 2000; Phillips & Meloy, 2012). Inclusive center-based ECE also provides the stage for children’s first encounters with unfamiliar peers and thus serves as a proving ground for the development of empathy, acceptance, tolerance, and social skills (Hauser-Cram et al, 1993; Killen et al, 2011; Odom et al, 2004; Stoneham, 2001).…”
Section: Double Vulnerability In Early Childhoodmentioning
confidence: 99%
“…There are reasons to believe that publicly funded center-based ECE serving low-income children and families may be just as-if not more-effective at boosting the school readiness skills of children with or at risk for special needs (referred to as "doubly vulnerable" herein; Guralnick, 1998) Inclusive approaches to early education have been found to enhance doubly vulnerable children's social and cognitive skills (Green et al, 2013;Holahan & Costenbader, 2000;Odom et al, 2004;Phillips et al, 2015;Phillips & Meloy, 2012). Moreover, relative to alternative ECE arrangements, ECE centers place a greater emphasis on school readiness skills; may be more likely to provide special educationspecific resources, such as therapists and psychologists (Essa et al, 2008;Henly & Adams, 2018;Weglarz-Ward & Santos, 2018); and may help ease transitions from preschool to kindergarten (Carlson et al, 2009;Rous et al, 2010).…”
mentioning
confidence: 99%
“…Studies have shown that both for children with and without special needs benefit from inclusive early childhood practices. Inclusive practices support social skills, language development, communication skills and friendship skills of children with special needs (Christensen-Sandfort and Whinnery, 2013;Green et al, 2014;Guralnick et al, 1996;Odom et al, 2006. In addition, typically developing children learn to accept and live with individuals with differences (Peck et al, 2004).…”
Section: Extended Summarymentioning
confidence: 99%
“…Studies have shown that both for children with and without special needs benefit from inclusive early childhood practices. Inclusive practices support social skills, language development, communication skills and friendship skills of children with special needs (Christensen-Sandfort and Whinnery, 2013;Green et al, 2014;Guralnick et al, 1996;Odom et al, 2006. In addition, typically developing children learn to accept and live with individuals with differences (Peck et al, 2004). According to data from the Ministry of National Education (MoNE) in Turkey, only 304 children with special needs received educational services in inclusive early childhood settings during the 2014-2015 school year while 1.631 children with special needs were educated in early childhood special education classrooms designed only for children with special needs.…”
Section: Extended Summarymentioning
confidence: 99%
“…Inclusion practices have more positive effects on the academic performance, social development and behaviours of the children with special needs in the inclusion settings (Buysse and Bailey, 1993;Lipsky and Gartner, 1996). For instance, language development and social skills of children are improving, and they make significant progress in early literacy skills when they take part in social inclusion programmes (Green, Terry and Gallagher, 2014;Rafferty, Piscitelli and Boettcher, 2003). Furthermore, they develop positive social interactions with their peers (Hollingsworth and Buysse, 2009), and there is also an increase in the level of their social acceptance (Odom et al, 2006).…”
Section: Sonuç Ve öNerilermentioning
confidence: 99%